Issue Notes - , Editor (Historical Papers, 2022)
The following papers were presented to the Canadian Society of Church History in 2008, but were not made available for publication: Julia Rady-Shaw, “Church Front: The Case of Bloor Street United Church’s War Effort, 1939-1945″; Gordon Heath, “When Friends and Neighbors Become Enemies: Canadian Baptists and the War of 1812″; Wolfgang Breul, “Martin Luther’s Development as a Reformer in Light of His own Statement from 1518: New Light on an Old Question”; Douglas H. Shantz, “Pietist Autobiography and the Rise of Secular Individualism”; Sarah Bruer, “Unselfish Devotion: Deaconess Zaidee Stoddard and the Social Gospel”; Kristin Burnett, “Acknowledging the ‘Unacknowledged Quarantine’: Religion, Faith, and Nursing at the Blood Hospital, 1893-1930s”; Renee Lafferty, “The ‘Spirits’ of Religion: Evangelicals and Medical Care for Toronto’s Dipsomaniacs, 1860-1890″; James Robertson, “‘T.T. Shields and the Des Moines Affair’: The Attempted Establishment and Subsequent Collapse of a Fundamentalist University in Des Moines, 1927-1929″; Ian Hesketh, “The Victorian Bible: Ecce Homo and the Manufacturing of a Literary Sensation”; Todd Webb, “‘Popery is Evidently Nodding to its Fall’: Methodism and Anti-Catholicism in British North America, 1837-1860.” Papers from a joint session with the Canadian Historical Association not made available for publication include: Marguerite Van Die, “Practising Medicine and Spiritualism in the 1860s: The Encounters Between Drs. Moses Colby and Susan Kilborn as Problem and Possibility in the Writing of Religious History”; Pamela E. Klassen, “The Holistic Trinity: Body, Mind, and Spirit among Twentieth-Century Protestants”; and Ruth Compton Brouwer, “When Missions Became Development: The Churches and CUSO in the 1960s – Linkages and Tensions.”